Heavy Metal Exposure and Psychiatric Disorders: Biological Mechanisms and Age-Related Differences - A Narrative Review - Klubikowska, Karolina; Tomczak, Barbara; Jelonek, Barbara; Porada, Dagmara; Twardowska, Daria; Żukowiecka-Sęga, Dominika; Topolski, Kamil; Wandzel, Małgorzata; Tłoczek, Wiktoria; Śliwa, Wiktoria (Journal of Education, Health and Sport, 2026)
Background: Mental disorders are among the leading causes of disability worldwide. Beyond genetic and psychosocial determinants, environmental factors such as heavy metal exposure are increasingly recognized as potential contributors to psychiatric risk. Persistent toxic metals may adversely affect central nervous system function across the lifespan. Aim: The aim of this review was to analyze current evidence on the association between heavy metal exposure and psychiatric disorders, with emphasis on biological mechanisms and age-related differences. Material and Methods: A narrative review of epidemiological, experimental, and clinical studies published up to 2024 was conducted using major scientific databases. The analysis focused on lead, cadmium, mercury, arsenic, and manganese. Results: Evidence indicates that heavy metal exposure is associated with neurodevelopmental disorders, cognitive impairment, depressive and anxiety symptoms, and, less consistently, psychotic manifestations. Proposed mechanisms include oxidative stress, neuroinflammation, neurotransmitter dysregulation, hypothalamic–pituitary–adrenal axis disruption, impaired neuroplasticity, and epigenetic changes. Children are particularly vulnerable during critical developmental periods, whereas chronic exposure in adults is more often linked to affective disorders and cognitive decline. Conclusions: Heavy metal exposure may represent a modifiable environmental factor contributing to psychiatric vulnerability. Further longitudinal research and improved exposure assessment are required to clarify causal relationships and support preventive strategies.